PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN BERBANTUAN APLIKASI GIMKIT PADA MATERI PEMBAGIAN BILANGAN CACAH SAMPAI 100 - Fiska Hafidzah Sabila; Lina Novita, Fitri Anjaswuri (STKIP Subang, 2025)
Fiska Hafidzah Sabila 037121052. Development of a Learning Evaluation Tool Assisted by the Gimkit Application on the Material of Division of Whole Numbers up to 100. This study aims to produce a learning evaluation tool product assisted by the Gimkit application on the material of division of whole numbers up to 100 in class IV-B SDN Cimahpar 2 with a total of 25 students. The development of this product uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study began by conducting observations and interviews related to needs analysis, curriculum analysis, student analysis, and product design. Then developing a learning evaluation tool product, conducting expert validation, and conducting a limited trial using the product on predetermined respondents. The results of the study from media experts, language experts, and material experts showed that this learning evaluation tool assisted by the Gimkit application was very valid and very feasible to use with an average percentage of 96.36%. At the trial stage, it was limited to 25 students, producing a very good response and was very interesting to use and obtained a percentage of 96%. Based on the research results, it can be concluded that the learning evaluation tool assisted by the Gimkit application on the material on dividing whole numbers up to 100 developed in this study is proven to be valid, interesting and motivating for students to use and is worth learning.